Approaches for teaching, learning and doing research as deduced from the Qur’an and Sunnah - AS, Basil; B, Sulaiman (IIUM Medical Journal Malaysia, 2009)
Approaches to teaching and learning keep on changing continuously as evidenced in the development of sub-disciplines dealing with education within the discipline, for example, medical education. This paper brings in another perspective in the search for the ideal teaching and learning approaches. Starting from the Qur’an and the Sunnah, this paper identifies about 20 different aspects of teaching and learning found in these two Islamic sources. These aspects could be grouped into four categories: pre-learning phase and setting the context; personality qualities needed for good teaching and learning relationship; teaching approaches; and lastly, approaches for enhancing the learning process. The paper demonstrates the great potential of the Qur’an and Sunnah for informing on the effective ways for teaching and learning.